Analisis Putusan tentang Permohonan Pailit oleh Pekerja akibat Tidak Terpenuhinya Hak Pesangon secara Keseluruhan Ditinjau dari Ketentuan Ketenagakerjaan dan Kepailitan - Olive Ozora Tesalonika Simanjuntak; Agus Mulya Karsona; Sherly Ayuna Putri (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
Indonesia is a country with a high level of labor-related issues, particularly in relation to the protection and fulfillment of workers’ rights. Common problems include termination of employment, unpaid wages, and inadequate severance payments. One such case is the bankruptcy petition filed against PT. Setiaji Mandiri, which serves as the focus of this study. The objective of this research is to analyze the legal considerations behind the Commercial Court’s decision to grant the bankruptcy request and its implications for labor rights. This study employs a normative juridical method by analyzing relevant legislation and court rulings, particularly referring to Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations, and Law No. 2 of 2004 on Industrial Relations Dispute Settlement. The findings show that PT. Setiaji Mandiri had indeed made efforts to settle its financial obligations, but these efforts were deemed insufficient by the court, leading to the acceptance of the bankruptcy petition. However, a key issue that emerged was the absence of debt registration with the Industrial Relations Court (PHI), which is mandated by law in cases involving employment disputes. According to the prevailing labor laws, the PHI must first determine the amount of severance pay owed to employees, which can then be used as a reference in bankruptcy proceedings. The study concludes that there was a procedural oversight in the handling of labor claims in this bankruptcy case. It emphasizes the importance of adhering to legal mechanisms that protect workers’ rights and recommends stricter coordination between commercial and labor courts to prevent similar issues in the future.